THE INFLUENCE OF CUSTOMER EXPERIENCE, UTILITARIAN BENEFITS, AND HEDONIC BENEFITS ON INTENTION TO RECOMMENDED (CASE STUDY ON KOPI JANJI JIWA BELITUNG) - Tresia Anggraini; Innocentius Bernarto (Universitas Pelita Harapan, 2021)
This study aims to examine the effect of customer experience on customer satisfaction, the effect of utilitarian benefits on customer satisfaction, the effect of hedonic benefits on customer satisfaction, the effect of customer experience on intention to recommend, the effect of utilitarian benefits on intention to recommend, the effect of hedonic benefits on intention to recommend, the effect of customer satisfaction on intention to recommend. This research was conducted using the incidental sampling method, from consumers of Kopi Janji Jiwa Belitung, Indonesia. This research was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of the Smart PLS program in testing the validity and reliability, as well as testing the hypothesis from the questionnaire used that has been distributed to 400 respondents. The results of this study indicate that customer experience, utilitarian benefits, and hedonic benefits affect customer satisfaction, then utilitarian benefits and customer satisfaction affect intention to recommend, but customer experience and hedonic benefits have no effect on intention to recommend.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menguji pengaruh customer experience terhadap customer satisfaction, pengaruh utilitarian benefit terhadap customer satisfaction, pengaruh hedonic benefit terhadap customer satisfaction, pengaruh customer experience terhadap intention to recommend, pengaruh utilitarian benefit terhadap intention to recommend, pengaruh hedonic benefit terhadap intention to recommend, pengaruh customer satisfaction terhadap intention to recommend. Penelitian ini dilakukan dengan metode penarikan sampel incidental sampling, dari konsumen Kopi Janji Jiwa Belitung, Indonesia. Penelitian ini dilakukan dengan menggunakan metode Partial Least Square-Structural Equation Modeling (PLS-SEM) dengan bantuan program Smart PLS dalam pengujian validitas dan reliabilitas, serta menguji hipotesis dari kuesioner yang telah disebarkan kepada 400 responden. Hasil penelitian ini menunjukkan bahwa customer experience, utilitarian benefit, dan hedonic benefit berpengaruh terhadap customer satisfaction, lalu utilitarian benefit dan customer satisfaction berpengaruh terhadap intention to recommend, akan tetapi customer experience dan hedonic benefit tidak berpengaruh terhadap intention to recommend.